Governance in Chinese Universities - Wen Wen; Simon Marginson (Emerald Publishing Limited, 2023)
This paper focuses on governance in higher education in China. It sees that governance as distinctive on the world scale and the potential source of distinctiveness in other domains of higher education. By taking an historical approach, reviewing relevant literature and drawing on empirical research on governance at one leading research university, the paper discusses system organisation, government–university relations and the role of the Communist Party (CCP), centralisation and devolution, institutional leadership, interior governance, academic freedom and responsibility, and the relevance of collegial norms. It concludes that the party-state and Chinese higher education will need to find a Way in governance that leads into a fuller space for plural knowledges, ideas and approaches. This would advance both indigenous and global knowledge, so helping global society to also find its Way.
10.1108/S0733-558X20230000086008; 10.1108/S0733-558X20230000086008; University Collegiality and the Erosion of Faculty Authority; EBP099697246